2014
DOI: 10.1152/ajpendo.00430.2013
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β mediates macrophage-induced impairment of insulin signaling in human primary adipocytes

Abstract: Adipose tissue expansion during obesity is associated with increased macrophage infiltration. Macrophage-derived factors significantly alter adipocyte function, inducing inflammatory responses and decreasing insulin sensitivity. Identification of the major factors that mediate detrimental effects of macrophages on adipocytes may offer potential therapeutic targets. IL-1β, a proinflammatory cytokine, is suggested to be involved in the development of insulin resistance. This study investigated the role of IL-1β … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
133
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(140 citation statements)
references
References 64 publications
(85 reference statements)
4
133
0
3
Order By: Relevance
“…The knockdown of NLRP3 by RNA interference significantly inhibited insulin resistance which is typically induced in PLIN2-overexpressing C2C12 cells, suggesting that the NLRP3 inflammasome mediates PLIN2-induced insulin resistance. Decreased levels of IRS-1 have been reported to alter insulin signaling in adipocytes and myocytes (24,25). In this study, we observed that IRS-1 expression was decreased in C2C12 cells that overexpressed PLIN2 in the context of insulin exposure, whereas NLRP3 knockdown increased the expression of IRS-1.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The knockdown of NLRP3 by RNA interference significantly inhibited insulin resistance which is typically induced in PLIN2-overexpressing C2C12 cells, suggesting that the NLRP3 inflammasome mediates PLIN2-induced insulin resistance. Decreased levels of IRS-1 have been reported to alter insulin signaling in adipocytes and myocytes (24,25). In this study, we observed that IRS-1 expression was decreased in C2C12 cells that overexpressed PLIN2 in the context of insulin exposure, whereas NLRP3 knockdown increased the expression of IRS-1.…”
Section: Discussionmentioning
confidence: 50%
“…3D). IL-1β, the final step in the NLRP3 inflammasome, has been demonstrated to reduce insulin-induced glucose uptake in adipocytes by affecting IRS-1 expression (18,25). To determine whether IL-1β treatment affects insulin-induced glucose uptake in myoblasts, we treated the C2C12 cells with IL-1β at concentrations of 0, 10, 25 and 50 ng/ml for 24 h prior to measuring insulin-induced glucose uptake.…”
Section: Suppression Of Irs-1 By Il-1β Mediates the Effects Of The Nlrp3mentioning
confidence: 99%
“…Macrophages themselves not only participate directly in the inflammatory response in adipose tissue being recruited as tissue mass expands in obesity (Weisberg et al, 2003;Xu et al, 2003), but they also stimulate the production of inflammation- stimulates the production of inflammation-related factors by adipocytes is essentially unknown, despite the central role of this cytokine in inflammation and disease processes in other tissues (Fietta et al, 2014;Lopalco et al, 2015). Nevertheless, IL-1β has been shown to be a regulator of IL-6 production by human preadipocytes (O'Hara et al, 2012), and to stimulate the expression and release of IL-6 and MCP-1 in human fat cells (Gao et al, 2014). IL-1β, like TNFα, is an adipokine, being synthesised and secreted by adipocytes themselves.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β has also been shown to stimulate the expression and release of several cytokines and chemokines, including IL-6 and MCP-1, and these changes are accompanied by down-regulation of the production of proteins in the insulin signalling pathway Gao et al, 2014). In the case of human pre-adipocytes, IL-1β has been identified as a key regulator of IL-6 production (O'Hara et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the presence of IL-1Ra restored the levels of phospho-Akt at early time points (1 and 2 hpw). IL-1b has been shown to significantly reduce the expression of phosphoinositide 3-kinase p85a and the phosphorylation of Akt, in adipocytes 53 ; hence, Il-1Ra may promote PI3K-Akt activation through suppression of IL-1b activity. Moreover, the lack of sustained activation of PI3K-Akt may contribute to the fact that the presence of IL-1Ra can only partially reverse some adverse effects of diabetes on the cornea wound healing.…”
Section: Il-1ra and Diabetic Cornea Wound Healingmentioning
confidence: 99%